2008
DOI: 10.2741/3175
|View full text |Cite
|
Sign up to set email alerts
|

Understanding eukaryotic linear motifs and their role in cell signaling and regulation

Abstract: It is now clear that a detailed picture of cell regulation requires a comprehensive understanding of the abundant short protein motifs through which signaling is channeled. The current body of knowledge has slowly accumulated through piecemeal experimental investigation of individual motifs in signaling. Computational methods contributed little to this process. A new generation of bioinformatics tools will aid the future investigation of motifs in regulatory proteins, and the disordered polypeptide regions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
300
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(308 citation statements)
references
References 167 publications
(132 reference statements)
7
300
0
1
Order By: Relevance
“…The EB1 binding affinities of many isolated MtLS sequences that we have tested are in the low/medium micromolar range, the best binders displaying a dissociation constant around 1 M. Such rather weak interactions are typical for short linear motifs that organize highly dynamic protein networks (43,44), reminiscent to the ones orchestrated by EBs at growing microtubule tips (4, 12-14). Interestingly, we found a good correlation between EB binding affinity and microtubule tip tracking activity in cells, further underpinning the conclusion that the EB-SXIP interaction is the underlying mechanism used by many ϩTIPs to target the growing microtubule plus-end.…”
Section: Discussionmentioning
confidence: 96%
“…The EB1 binding affinities of many isolated MtLS sequences that we have tested are in the low/medium micromolar range, the best binders displaying a dissociation constant around 1 M. Such rather weak interactions are typical for short linear motifs that organize highly dynamic protein networks (43,44), reminiscent to the ones orchestrated by EBs at growing microtubule tips (4, 12-14). Interestingly, we found a good correlation between EB binding affinity and microtubule tip tracking activity in cells, further underpinning the conclusion that the EB-SXIP interaction is the underlying mechanism used by many ϩTIPs to target the growing microtubule plus-end.…”
Section: Discussionmentioning
confidence: 96%
“…As suggested by others, through parallel or convergent evolution, such MoRFs can exist as conserved functional motifs or regions among various species, such as human, mouse, yeast, E. coli, or even viruses. 79 As pointed out previously, 77 such short linear motifs are amenable to convergent evolution due to the limited number of mutations that are necessary for the generation of a useful motif. In fact, motifs are commonly used as adding new functional modules within a proteome, especially in higher eukaryotes.…”
Section: Discussionmentioning
confidence: 97%
“…47,75,77,78 Instead, our approach here is to investigate fewer MoRF examples, but in greater detail in order to develop a deeper understanding of how IDPs can alter their conformations so as to be able to bind to structurally distinct partners. Our observations demonstrated that, in general, conformation flexibility allows for both subtle and complex structural variation, thereby enabling the same sequence to transform onto the diverse and distinctively shaped binding sites provided by their partners.…”
Section: Discussionmentioning
confidence: 99%
“…DynaMine has the ability to outline molten globule regions (for example, NCBD or CBP) embedded in a more disordered structural environment. IDPs often recognize their binding partners via short continuous sequence motifs, which are frequently defined by local sequence conservation 38,39 and structural bias towards the bound conformational state [6][7][8] . DynaMine seems to be capable of picking up locally reduced dynamics in these regions, which appear as peaks in the prediction.…”
Section: Discussionmentioning
confidence: 99%